Vojtov V.A., Bekirov A.SH., Voitov A.V. Criteria for evaluation of tribus system practices and its communi-cation with tribological characteristics. - Войтов, В. А.; Бекиров, А. Ш.; Войтов, А. В. (Problems of Tribology, 2018)
The definition of the quality factor of the tribosystem was further developed, which, unlike the known, takes into account the geometric dimensions and kinematic scheme of the tribosystem, the thermal diffusivity of materials and the rate of propagation of deformation in the surface layers of the triboelement materials in the course of their contact interaction. Theoretical and experimental studies have established a relationship between the Q-factor, the wear rate and the friction coefficient in the process of running-in. It is shown that an increase in the quality factor reduces the above parameters, and the criterion itself is a measure of the potential ability of a tribosystem to adapt (adapt) to operating conditions